On the Role of the Theatrical Agent in Operatic Circuits at the Turn of the Twentieth Century: The Case of the Eastern Adriatic Coast - Cristina Scuderi (De Musica Disserenda, 2021)
The article examines the role of the theatrical agent in the operatic circuits of the late nineteenth and early twentieth centuries on the eastern Adriatic coast in the light of his relations with theatre management, impresarios and fellow agents. There were many different types of theatrical agent involved in managing operatic seasons, and they had different working practices.